2021
DOI: 10.1371/journal.pone.0249006
|View full text |Cite
|
Sign up to set email alerts
|

Unhygienic stool-disposal practices among mothers of children under five in Cambodia: Evidence from a demographic and health survey

Abstract: Background Unhygienic disposal of children’s stools affects children’s health in terms of their susceptibility to many diseases. However, there are no existing studies into the impact of unhygienic stool disposal in Cambodia. Therefore, this study aimed to identify factors associated with the unhygienic disposal of children’s stools among children under the age of five in Cambodia. Methods An analytical cross-sectional study was conducted using data from the Cambodia Demographic and Health Survey (CDHS) 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 17 publications
8
8
2
Order By: Relevance
“…The level of safe CFD revealed in this study is comparable to that found in a study conducted in Madagascar (38%), 30 and Ethiopia. 21 However, the proportion of CFD practice in the current study was lower than studies of Zambia (77.81%), 21 Nigeria (56.95%), 21 Malawi (84.67%), 21 Kenya (70%), 31 Malawi (79%), 32 Mali (63.5), 21 Cambodia (70.73%), 33 and Uganda (75%). 34 This difference might be due to socio-demographic, environmental, cultural, institutional, economic, and individual livelihood factors of the current study compared to the previous settings.…”
Section: Discussioncontrasting
confidence: 66%
“…The level of safe CFD revealed in this study is comparable to that found in a study conducted in Madagascar (38%), 30 and Ethiopia. 21 However, the proportion of CFD practice in the current study was lower than studies of Zambia (77.81%), 21 Nigeria (56.95%), 21 Malawi (84.67%), 21 Kenya (70%), 31 Malawi (79%), 32 Mali (63.5), 21 Cambodia (70.73%), 33 and Uganda (75%). 34 This difference might be due to socio-demographic, environmental, cultural, institutional, economic, and individual livelihood factors of the current study compared to the previous settings.…”
Section: Discussioncontrasting
confidence: 66%
“…Azage & Haile 2015;Cronin et al 2016;Bawankule et al 2017;Islam et al 2018;Aliyu & Dahiru 2019;Sahiledengle 2019Sahiledengle , 2020Seidu et al 2020Seidu et al , 2021Simelane et al 2020;Getahun & Adane 2021;Soboksa 2021;Soboksa et al 2021;Vong et al 2021), while 6 studies were of moderate(Wilunda & Alessio 2009;Siruri 2013;Mihrete et al 2014;Aluko et al 2017;Sidabalok et al 2019;Alemayehu et al 2021) according to our assessment (Supplementary Material, Table…”
mentioning
confidence: 81%
“…The highest prevalence was reported in Nigeria (80.33%) (Aluko et al 2017), Bangladesh (80.33%) (Islam et al 2020), and India (79.00%) (Bawankule et al 2017). In contrast, studies from Ethiopia (9.20%) (Alemayehu et al 2021), Kenya (30%) (World Bank/UNICEF 2015), and Cambodia (29.27%) (Vong et al 2021) reported the lowest prevalence.…”
mentioning
confidence: 93%
See 2 more Smart Citations